Adenoma detection rate for screening colonoscopy: one center experience - Pilvinytė, Laura; Mašalaitė, Laura; Stanaitis, Juozas (Lietuvos chirurgija, 2017)
Objective Adenoma detection rate (ADR) is a recommended quality measure for screening colonoscopies in risk population. The main aim of our study was to calculate ADR in Vilnius University Hospital Santariskiu Klinikos (VUH SK) and determine inter-individual variations among practicing endoscopists. Material and methods Retrospective data review of all the patients who underwent screening colonoscopy in the VUH SK (Vilnius, Lithuania) between 2009 and 2012. Results A total of 1633 colonoscopies, which were performed by five practicing endoscopists were included. The overall cecal intubation rate was 96.8%. Bowel preparation was good, medium and poor in 65.2%, 28.1% and 6.7% cases, respectively. Polyps were found more commonly in men rather than women: adenomas 40.4% vs. 24% (p<0.001), hyperplastic polyps 11.1% vs. 6.6% (p=0.001), multiple adenomas 6.4% vs. 1.9% (p<0.001). Colorectal cancer was found in 76 patients (4.7%) and there was no statistically significant difference regarding sex (p=0.76). The overall ADR was 31.5%. ADR in men was statistically significantly higher compared with ADR in women (40.4% vs. 24%; p<0.001). ADR ranged among endoscopists from 26.8% to 36.5% (p=0.007). Overall multiple adenoma detection rate was 4% and ranged among endoscopists from 1.7% to 6.7% (p=0.03). Mean number of adenoma per procedure was 0.5 and mean number of adenoma per positive procedure was 1.59. Conclusions Adenoma detection rate in our center is high. Based on current recommendations ADR detected is sufficient for reporting high quality screening colonoscopy.